Pengaruh Kejelasan Sasaran Anggaran, Sistem Keuangan Desa Terhadap Akuntabilitas Pengelolaan Dana Desa Dengan Kompetensi Aparat Pengelola Dana Desa Sebagai Variabel Moderasi Pada Kantor Desa Se-Kecamatan Banjarangkan Kabupaten Klungkung - Yani, Ni Luh Made Wisna; Kusumawati, Ni Putu Ayu; Hutnaleontina, Putu Nuniek (Hita Akuntansi dan Keuangan, 2024)
This research looks at how the responsibility of managing village funds with the competency of village fund management officials is affected by the specificity of budget aims and the structure of the village financial system. Thirteen village administration centres in Banjarangkan Klungkung were visited for this study. There were a total of 39 participants. Using the Smart PLS programme, we do a structural equation modelling PLS analysis of the data. The findings demonstrated that the responsibility of village fund administrators was positively and significantly impacted by the clarity of budget proposals. Accountability in the handling of village funds was improved somewhat by the use of the village financial system (siskeudes). The responsibility of village fund managers is not enhanced by the competency of village fund management officials due to the clarity of budget aims and the local financial system.